DEVELOPMENT AND VALIDATION OF HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY METHOD FOR THE ESTIMATION OF POSACONAZOLE IN FORMULATION - jain, vandana; Nikam, Shubham (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The study aims to developed and validate novel high performance thin layer chromatographic method for estimation of posaconazole in tablet dosage form and validate as per the international conference on harmonization (ICH) guidelines. Methods: The method was developed on silica gel 60 F254 HPTLC plates and the mobile phase was used as toluene: chloroform: ethanol in ratio (5:4:1 V/V/V). Densitometric analysis of Posaconazole was performed at the wavelength 265 nm. Results: The RF of Posaconazole was found to be 0.331. The calibration curve was found to be linear in the concentration range of 100–500 ng/band. The correlation coefficient is 0.9991 for Posaconazole. The precision result was found to be satisfactory, which indicate that the method is precise. The recovery value lies in the range of 98–102% indicating the accuracy of the method. Conclusion: A new, simpleaccurate, fast, economic, precise, and robust high performance thin layer chromatographic method was developed for the estimation of Posaconazole. The method is selective, specific it was applied in pharmaceutical analysis of Posaconazole tablet dosage form.